Cognitive stress and its relation to the motivation of achievement and academic compatibility among a sample of university students - Al-Zahrani, Ahmed Saleh Mousa (Journal of Educational and Psychological Sciences, 2018)
The objective of the study was to identify the correlative relations between the perceived psychological pressures and the motivation of achievement and academic compatibility among the students of Jeddah University. The researcher used the descriptive descriptive method. The study tools were represented in the cognitive stress scale. Preparation of Alazmi 2013 - The Academic Accuracy Scale for University Students - Prepared by Adaily 2016 - Applied to a random sample of 150 students from the University of Jeddah with 28.8% of the original community; Special Education, , Quranic studies) Palm Stages (4, 5, 6, 7). The average age of time was 21.52. The study found the following results: A low level of perceived psychological pressure in the sample with an average of 2.51 and a motivation level of achievement of 3.38. . The results of the study also showed that there is a negative correlative relationship between the psychological pressures of different types and the motivation of achievement in their various dimensions and the existence of a negative correlative relation between the psychological pressures of different types and academic compatibility in different fields. The results of the study indicated that there was a statistical contribution to both perceived psychological pressures and achievement motivation in predicting the academic compatibility of university students. In the light of the results of the study, a number of recommendations and suggestions were presented to alleviate the psychological pressure and increase the motivation for achievement and academic compatibility among a sample of university students.